Mill's closet: J.S. Mill on solitude and the imperfect democracy. Issue 1 (2nd January 2019) - Paltieli, Guy
ABSTRACT: This paper focuses on the role solitude played in John Stuart Mill's political thought. By doing so, it challenges contemporary appropriations of Mill's thought by participatory, deliberative and epistemic theories of democracy. Mill considered solitude to be contrary to political participation and public debate, but nonetheless regarded it as essential for democracy and for intellectual progress. Since the early 1830s Mill began developing an idea of solitude while simultaneously forming a particular kind of a democratic model which I refer to as 'imperfect democracy'. According to this model, democracy is restrained by non-democratic elements which offer a contrary spirit and are not incorporated by democracy. At first Mill believed the 'leisured class' would fulfil this task, but later considered solitude as a possible solution. This paper follows the way in which these ideas were crystallised in Mill's thought, and by doing so offers a novel interpretation of Mill's political thought and his nuanced understanding of solitude, political participation and democracy.